‘Caught between a rock and a hard place’ - Andreas Anderberg (Nordisk Tidsskrift for Kriminalvidenskab)
The societal approach towards juvenile offenders have, in a Nordic context, focused on care and treatment rather than punishment. As juvenile delinquency is seen as an ever-increasing problem, the social law efforts have been deemed insufficient by politicians and more emphasis has been placed on measures of criminal justice. Furthermore, procedural regulations have been subject to reform proposals in a repressive direction. At the same time, children’s rights have been strengthened for example by the UN Convention of the Rights of the Child becoming Swedish law. The legal consequences for juvenile offenders are thus a complex field of tension, in the middle of legal areas with often diametrically opposed goals and strategies. The question has also been raised whether juvenile offenders should be dealt with, within an entirely separate system. The purpose of this essay is to illustrate the conflict area and show a development in the legislature on juvenile offenders. Also, the question whether the increasingly repressive measures are compatible with children’s (human) rights is raised. The essay is based on Swedish conditions, but since Swedish legal debate in recent years have been strongly influenced by (sometimes questioned) Danish reforms such as e.g. lowering the age of criminal responsibility and introducing special Youth Crime Boards, Denmark will serve as a natural point of comparison.